2010
DOI: 10.1021/jp908839r
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Synthesis of Hierarchical Nickel and Morphology-Dependent Electromagnetic Properties

Abstract: Nickel nanomaterials with a wide range of morphologies and sizes, such as superfine nanoparticles, urchinlike chains, smooth chains, rings, and hexagonal Ni/Ni(OH)2 heterogeneous structure plates, are synthesized in a single reaction system by simply adjusting the reaction conditions. The morphology transformation mechanism is systematically investigated. Magnetic measurement of urchinlike chains, smooth chains, and rings shows that the saturation magnetization (M s) decreases with reduced sample size, and rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
128
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 207 publications
(133 citation statements)
references
References 31 publications
5
128
0
Order By: Relevance
“…7. It is well known that the ε′ and μ′ values stand for the storage ability of electromagnetic energy while the ε′′ and μ′′ values stand for the dissipation of energy [27]. In Fig.…”
Section: Resultsmentioning
confidence: 99%
“…7. It is well known that the ε′ and μ′ values stand for the storage ability of electromagnetic energy while the ε′′ and μ′′ values stand for the dissipation of energy [27]. In Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Among many microwave absorbers, the metallic so magnetic materials of cobalt and nickel have attracted great attention, due to their good conductivity, high saturation magnetization, high permeability at GHz frequency ranges, as well as low manufacturing cost. [15][16][17][18][19] However, the permeability might have a rapid decrease in high frequency due to eddy current losses induced by the electromagnetic wave. 20 There are two solutions to solve the problem.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al reported morphology-dependent electromagnetic properties and urchinlike nickel chains exhibited the best absorption performance with a peak of À25.29 dB at 9.6 GHz. The strong absorption was quantitatively illustrated as geometrical effect, multiple-absorption and point discharge effect due to the urchinlike microstructure [9]. Sun et al has reported the morphology-dependent magnetic properties on iron-based dendrite-like materials with the reflection loss from À53 to À25 dB.…”
Section: Introductionmentioning
confidence: 99%